Topological properties of the Fréchet space of holomorphic functions of several complex variables - Iida, Yasuo (Mathematica Montisnigri, 2023)
Let p( n) ( > 1) be the Privalov class of holomorphic functions on the unit ball n in the space of -complex variables. The class p( n) ( > 1), equipped with the topology given by a natural metric, becomes an -algebra. In this paper, we shall introduce a Fréchet space Fp( n) ( > 1) of holomorphic functions on n which contains p( n). Moreover, we shall characterize some topological properties of Fp( n) induced by the family of semi norms on Fp( n) .